Finding the balance: comparing the effectiveness of student-managed and teacher-directed learning in science classes. - Bell, Colin R. (Curtin University, 2000)
The purpose of the research was to form a defensible basis for considering possible changes in classroom practice within a small rural state school, and it involved four, mixed-ability classes comprising Year 9 and 10 students. These classes were taught an energy-related module by the researcher. In the preliminary phase, which involved two classes, resources were developed to produce a more student-centred module. These resources, and the constructivist approach which informed their development, are described. In the subsequent comparative phase, the reformed module was taught using two contrasting strategies - one teacher-directed and the other, student-managed. During this phase individual achievement and group investigative skills were assessed. Student perceptions of classroom environment were probed using an existing instrument, the ICEQ. The range of classroom activity and level of student engagement was continuously monitored by independent observers using a specifically developed instrument, termed the SALTA.No overall learning advantage was demonstrated to either teaching strategy. A small strategy advantage favouring Year 10 students in the student-managed strategy was offset by a similar disadvantage to the Year 9 cohort. A cohort penalty was found to apply to Year 9 students under either strategy, with a paradox in its application. The role of the teacher was found to change significantly under each strategy, with a consistent hierarchy of student engagement with activity emerging. Boys were found to have significantly higher levels of engagement than girls under either teaching strategy. However, this was associated with only modest advantages in achievement. The relationship between engagement and achievement was stronger and more positive under the student-managed strategy. Mismatches between preferred and actual classroom environment were found, particularly in the dimension of independence. This mismatch was less in the student-managed setting. Increased potential for learning was noted under each strategy.